Quality of life, delinquency and psychosocial functioning of adolescents in secure residential care: testing two assumptions of the Good Lives Model - C. S. Barendregt; A. M. Van der Laan; I. L. Bongers; Ch. Van Nieuwenhuizen (BMC, 2018)
Abstract Background In this study, two assumptions derived from the Good Lives Model were examined: whether subjective Quality of Life is related to delinquent behaviour and psychosocial problems, and whether adolescents with adequate coping skills are less likely to commit delinquent behaviour or show psychosocial problems. Method To this end, data of 95 adolescents with severe psychiatric problems who participated in a four-wave longitudinal study were examined. Subjective Quality of Life was assessed with the ten domains of the Lancashire Quality of Life Profile and coping skills with the Utrecht Coping List for Adolescents. Results Results showed that adolescents who reported a lower Quality of Life on the health domain had more psychosocial problems at follow-up. No relationship was found between Quality of Life and delinquent behaviour. In addition, active and passive coping were associated with delinquent behaviour and psychosocial functioning at follow-up. Conclusions Based on the results of this longitudinal study, the strongest support was found for the second assumption derived from the Good Lives Model. Adolescents with adequate coping skills are less likely to commit delinquent behaviour and have fewer psychosocial problems at follow-up. The current study provides support for the use of strength-based elements in the treatment programmes for adolescents in secure residential care.